THE COMMUNICATION TRENDS REFERRING TO KAZAKHSTAN’S INTERNATIONAL IMAGE: The case of The Washington Post - Skpipnikova, Anastasiya; Zhanibek, Azel; Negizbayeva , Marlan; Mukan , Saken; Saudabekova, Elmira (Brazilian journalism research, 2025)
ABSTRACT – The research analyzes journalistic materials published in The Washington Post that mention Kazakhstan from 1991 to 2017. Using content analysis as the primary research method, both quantitative and qualitative evaluations were conducted to gain historical insights. The study found that the highest number of publications occurred in 2013 and 2014. However, despite the increase in publications, it was observed that many articles were uninformative and did not contribute to the formation of a specific image of the country. Efforts to generate interest and build a positive narrative about Kazakhstan were not successful. The study also examined readers’ comments online and concluded that perceptions of the country are still largely influenced by stereotypes. RESUMO – A pesquisa tem como objetivo analisar materiais jornalísticos publicados no jornal The Washington Post que mencionam o Cazaquistão de 1991 a 2017. A análise de conteúdo é o principal método de pesquisa, permitindo operações quantitativas e qualitativas e fornecendo valiosas percepções históricas ao longo do tempo. De acordo com os resultados, o maior aumento de publicações foi observado em 2013 e 2014, respectivamente. Um número maior de publicações não afeta a formação de uma determinada imagem do país; os artigos foram classificados como não informativos. Os eventos de construção de imagem no Cazaquistão, que foram planejados para causar um aumento de interesse, infelizmente não produziram o efeito desejado. Foram analisados não apenas os textos jornalísticos, mas também as respostas a eles, em especial os comentários dos leitores on-line. Essa parte do estudo levou à conclusão de que a percepção do país ainda se baseia em estereótipos. RESUMEN – La investigación tiene como objetivo analizar los materiales periodísticos publicados en el diario The Washington Post que mencionan Kazajstán desde 1991 hasta 2017. El análisis de contenido es el principal método de investigación, que permite operaciones tanto cuantitativas como cualitativas y proporciona valiosas perspectivas históricas a lo largo del tiempo. Según los resultados, el mayor aumento de publicaciones se observó en 2013 y 2014, respectivamente. Un mayor número de publicaciones no influye en la formación de una determinada imagen del país; los artículos se clasificaron como poco informativos. Los eventos de creación de imagen en Kazajistán, que estaban diseñados para causar un aumento del interés, lamentablemente no produjeron el efecto deseado. No sólo se analizaron los textos periodísticos, sino también las respuestas a los mismos, en particular, los comentarios de los lectores en línea. Esta parte del estudio llevó a la conclusión de que la percepción del país sigue basándose en estereotipos.